Tinjauan Literatur Peran Teknologi Digital Dalam Bisnis: Dampak Disruptif TI Pada Perusahaan - Larasati Pingkan Cahya Hernita; Agussalim (Lembaga Pengembangan Kinerja Dosen, 2024)
This article presents a literature review on the role of digital technology in business and its disruptive impact on companies. We analyze how digital technology drives business transformation, enhances operational efficiency, and fosters innovation in products and services. However, the use of digital technology also brings disruptive effects, compelling companies to adapt to changes in business models and increased competition. This article provides valuable insights for business practitioners and decision-makers on how to effectively manage the impact of digital technology.